Pendampingan Karang Taruna Desa Sahang melalui Budaya Nyinom dalam Membentuk Karakter Gotong Royong - Sofi Ahmad Al-Farisi; Lisma Meilia Wijayanti (Social Science Academic, 2025)
The nyinom (sinoman) tradition is a social heritage of Javanese society rooted in the values of mutual cooperation, solidarity, and selfless service. In Sahang Village, this tradition is not merely a social practice within communal celebrations but also functions as a character education mechanism based on local wisdom. Through the involvement of young people in nyinom activities, values of identity, morality, and competitiveness are naturally cultivated within community life.The urgency of this tradition becomes increasingly relevant when confronted with the challenges of globalization and the pervasive influence of digital culture, which often weaken social interaction and solidarity among citizens. From an interdisciplinary perspective, nyinom can be understood as a bridge between the past and the future: it safeguards the continuity of noble values while serving as an instrument for shaping the character of youth within the Karang Taruna organization. Drawing on recent academic literature (2015–2023), this paper argues that nyinom is not merely a cultural tradition but also a moral bulwark capable of addressing the character crisis among younger generations. Therefore, the revitalization of nyinom becomes a crucial agenda in the development of character education grounded in local wisdom in the digital era.